1991
DOI: 10.1159/000173392
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Rat Kidney Morphology between Males, Females and Testosterone-Treated Females

Abstract: Kidneys of normal female and male Wistar-Kyoto rats were studied by standard morphological techniques and morphometry in order to evaluate possible differences in the overall kidney morphology between both sexes. Furthermore, we investigated the role of testosterone (DHT) on kidney morphology by treating females with daily DHT injections. Kidney weight and volume in relation to body weight were not significantly different between males and females and were not affected by DHT. Differences were found in the vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
32
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 20 publications
5
32
0
1
Order By: Relevance
“…Anatomic studies have documented larger kidney weight in men (28), but the results were inconsistent when the kidney size was corrected for body surface area (16,28). In animals, kidney size and weight is greater in males (7,29), even when corrected for body weight (29,30). Information on the number of glomeruli in the two genders is also conflicting: (1985 to 2000); actuarial graft survival.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomic studies have documented larger kidney weight in men (28), but the results were inconsistent when the kidney size was corrected for body surface area (16,28). In animals, kidney size and weight is greater in males (7,29), even when corrected for body weight (29,30). Information on the number of glomeruli in the two genders is also conflicting: (1985 to 2000); actuarial graft survival.…”
Section: Discussionmentioning
confidence: 99%
“…Rats are frequently used in animal experiments, and there have been many reports regarding the sex differences in the morphology and function of the rat kidneys; e.g., the segmentation of nephrons [13], the thickness of each of the renal zones [16], the ultrastructural features of the proximal tubular epithelium [21,27], the concentration and constituents of the urine [1,11,16], and the structural and functional alterations with aging [3,6,18,22]. The effects of castration and sex hormone-treatment in the rat kidneys have also been investigated, and the effects on the size of the glomeruli and proximal tubules [14], ultrastructural features of the proximal tubular epithelium [21,27], concentration and constituents of urine [11,16], and the severity of glomerular damage with aging or after uninephrectomy [3,5,15,19,20], have been reported.…”
mentioning
confidence: 99%
“…The effects of castration and sex hormone-treatment in the rat kidneys have also been investigated, and the effects on the size of the glomeruli and proximal tubules [14], ultrastructural features of the proximal tubular epithelium [21,27], concentration and constituents of urine [11,16], and the severity of glomerular damage with aging or after uninephrectomy [3,5,15,19,20], have been reported. Regarding the strain differences, several reports demonstrated the strain differences in the urinary constituents [1], glomerular filtration rate (GFR) [7], renal plasma flow (RPF) [7], pathological changes with aging [6,18,22], and the sensitivity to nephrotoxicity due to chemical drugs [4,17] and high-protein food [12].…”
mentioning
confidence: 99%
“…5B). Oudar et al (1991) reported a gender difference in the relative volume of both the cortex and medulla with regard to the total kidney volume. The difference in the relative volume of the medulla was at most 2-fold greater in female than in male rats and could have a minor effect on the observation of higher Oatp1 expression in male than in female rats.…”
mentioning
confidence: 99%